2014
DOI: 10.1021/ie502057k
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Modeling Analysis of Dual-Reflux Pressure Swing Adsorption Process

Abstract: A laboratory-scale dual-reflux pressure swing adsorption process unit comprised of two beds with intermediate feed position was built and tested for concentrating dilute gaseous feed of methane in nitrogen using Norit RB1 activated carbon. Experimental investigations revealed that the change in blowdown or pressurization step time, feed or purge step time, and heavy product flow rate did not have a significant effect on process performance (in terms of methane purity). However, the process performance was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Methane recovery to the heavy product was highest in Runs 1, 3, 5, 19 and 20. The experiments of Bhatt et al [24] were conducted with a similar carbon adsorbent and a feed composition of 5 mol% CH 4 and produced average CH 4 and N 2 products of 58 mol% and 98 mol% purity, respectively. The results of the separations reported by Bhatt et al are also shown in Fig.…”
Section: Separation Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Methane recovery to the heavy product was highest in Runs 1, 3, 5, 19 and 20. The experiments of Bhatt et al [24] were conducted with a similar carbon adsorbent and a feed composition of 5 mol% CH 4 and produced average CH 4 and N 2 products of 58 mol% and 98 mol% purity, respectively. The results of the separations reported by Bhatt et al are also shown in Fig.…”
Section: Separation Performancementioning
confidence: 99%
“…The light reflux and heavy product flow rates were varied in each experiment, which changed the separation performance as indicated by the arrows. The results obtained by Bhatt et al are also plotted[24].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…1; Saleman et al 2015;Zhang et al 2016;May et al 2017) and the light recycle ( ̇n LR in Fig. 1; Bhatt et al 2014;Shen et al 2017;Zhang et al 2016;Tian et al 2017;Li et al 2016) have been identified as major operating parameters to tune the product purity. On the other hand, the effect of changing the pressure ratio, , has not been systematically investigated, even though it can be expected to affect significantly the DR-PSA process performances.…”
Section: Process Performance Improvementmentioning
confidence: 99%
“…Similar efforts towards the design of the best process conditions have been made on the modelling side. Different models have been proposed, ranging from detailed models requiring numerical solutions (Rossi et al 2019a, b;Zou et al 2017;May et al 2017;Bhatt et al 2014;Thakur et al 2011) to simplified semi-analytical models based on the so called Equilibrium Theory (Bhatt et al 2018(Bhatt et al , 2017(Bhatt et al , 2013Kearns and Webley, 2006a, b). In the latter case, the design conditions which allow the complete separation of binary mixtures in the case of linear isotherms have been investigated (Bhatt et al 2013(Bhatt et al , 2015(Bhatt et al , 2017(Bhatt et al , 2018 and two key process parameters have been identified: the capacity ratio C , proportional to the ratio between the number of moles injected during the adsorption step and the volume of the column, and the dimensionless feed injection position z feed .…”
Section: Introductionmentioning
confidence: 99%